POLITICAL RADIO ADVERTISEMENT AND VOTERS’ CHOICE OF CANDIDATE DURING ELECTIONS IN NIGERIA - Alade, Moyosore; Shakirat Ifedolapo, Adebisi; Olusola Ayinde, Lawal; Ebenezer Odion, Victor (African Journal of Social and Behavioural Sciences, 2024)
This study investigates the influence of political radio advertisements on civil servants’ voting choices during the 2022 Osun State Gubernatorial election, exploring the effectiveness of this campaign amidst low voter turnout. The study employed a survey research design through the use of a questionnaire, which was used to gather data among civil servants in the Ede North Local Government, with a sample size of 173 respondents. The findings indicate that while respondents frequently engage with radio content, their assessment of the educational and persuasive quality of political ads is moderate. Notably, ads were seen as critical of opponents, yet their influence on voters’ choices was ambiguous, with many respondents indicating a limited impact on their electoral decisions. This aligns with previous studies emphasizing the dual role of media in both informing and influencing voter behaviour. The research highlights the complexities of political advertising in shaping electoral outcomes and offers recommendations for more effective communication strategies tailored to the electorate’s needs in Nigeria’s evolving political landscape.